Association of Vitamin E with Rapid Thawing on Goat Semen - Jurandy Mauro Penitente-Filho; Fabrício Albani Oliveira; Carolina Rodriguez Jimenez; Erly Carrascal; Júlio César Oliveira Dias; Gisele Dias Oliveira; Renata Gomes Silveira; Camila Oliveira Silveira; Ciro Alexandre Alves Torres (The Scientific World Journal)
The aim of this study was to evaluate the effects of vitamin E associated with rapid thawing on cryopreserved goat semen. Two bucks were used and eight ejaculates per animal were collected using artificial vagina. Semen was diluted with the following treatments: BIOXCELL (control), BIOXCELL + Equex (sodium lauryl sulphate) and BIOXCELL + vitamin E 100 μM. Semen was packaged into 0.25 mL straws and cooled at 5°C for 1 hour. Freezing was performed in liquid nitrogen vapor (−155°C) during 15 minutes. Then, the straws were immersed in liquid nitrogen (−196°C). Straws were thawed at 38°C/60 seconds or at 60°C/7 seconds with immediate sperm analysis. Hypoosmotic swelling test was performed adding a 20 μL aliquot of thawed semen to 1 mL of hypoosmotic solution (100 mOsm·Kg−1) followed by incubation during 60 minutes in water bath (38°C). Vitamin E did not affect any studied parameters (P>0.05). Nevertheless, defrosting rate of 60°C/7 seconds improved sperm membrane functional integrity (P<0.05). Current knowledge about goat semen cryopreservation is not sufficient to ensure high post-thawing recovery rates; thus, this study brings important data about using antioxidants and different thawing rates on cryopreservation process.